Introduction: Biodiversity, Biotechnology, and the Legal Protection of Traditional Knowledge - Charles R. McManis (Washington University Journal of Law & Policy, 2005)
This symposium volume is composed of five articles that were originally presented as papers at a conference, held at Washington University School of Law on April 4–6, 2003, on the general topic, “Biodiversity, Biotechnology, and the Legal Protection of Traditional Knowledge,” as well as a concluding article which discuss an important post-conference development at Washington University School of Law. Like the conference itself, these articles address the three general topics that are implicit in the title of the conference and this symposium volume.
Keywords: Biodiversity; Biotechnology; Traditional knowledge